EFEKTIVITAS EKSTRAK ETANOL DAUN SALAM (Syzygium polyanthum (Wight) Walp.) SEBAGAI PENGAWET ALAMI ANTIMIKROBA - Husnul Warnida; Yullia Sukawaty (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2016)
Preservative is an additive substance to protect products from microbial contamination. Consumer demand for preservative-free products has encouraged the development of cosmetic products with natural preservative. Bay leaves (Syzygium polyanthum (Wight) Walp.)) have potential as a natural preservative. This study aimed to test the effectiveness of the Bay leaves ethanol extract as an antimicrobial preservative in cream using antimicrobial preservatives testing procedures according to the Indonesian Pharmacopoeia Edition IV. Bay leaves are extracted using ethanol 95%. Bay leaf extract formulated into cream with concentration of 5% and 10%. Pour plate method and calculation of the number of bacteria by plate method has conducted on the effectiveness of antibacterial preservative. Percent mortality after 14 days observation of the Escherichia coli and Staphylococcus aureus respectively on formula A are 94.00% and 84.55%, while formula B are 97.28%, and 92.76%. It can be concluded that the bay leaves ethanol extract concentrations of 5% and 10% was ineffective as an antimicrobial preservative according to the Indonesian Pharmacopoeia Edition IV